Clinicohistopathological Features and Treatment Outcomes of Neuroendocrine Tumors; A Single Center Experience - Sumbul, A. T.; Sedef, A. M.; Kose, F.; Mertsoylu, H.; Sezer, A.; Ozyilkan, O.; Abali, H. (KARGER, 2017)
14th Annual ENETS Conference for the Diagnosis and Treatment of Neuroendocrine Tumor Disease, Barcelona, SPAIN, MAR 08-10, 2017
Keywords: neuroendocrine tumors; single center